2020
DOI: 10.33899/ijvs.2019.125660.1124
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, morphological and biochemical study of larval stage Coenurus cerebralis of Taenia multiceps in sheep

Abstract: This study aimed to estimate the prevalence of Coenurus cerebralis of Tenia multiceps in sheep of Nineveh governorate. One handed and thirty-six sheep heads were examined for the presence of coenurus cysts 31 (22.8%) were infected. The younger were more affected than the adults. There were no significant differences between the number of infected males and females. The clinical signs varied from one animal to another which consisted of neurological disorders manifested by depression, bending of the head to one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…This study found that the total infection rate was 23.68% in Iraq. This result is apparently similar to that obtained in Iraq [2], Turkey [19], and Iran [20], lower than recorded in Ethiopia [21] and Egypt [22], and higher than carried out in India [23] and Jordan [24]. This variation in the prevalence of disease may reflect the different management systems, the amount of contamination of the pastures with the tapeworm eggs, and the attempts for controlling and preventing infection [25,26].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study found that the total infection rate was 23.68% in Iraq. This result is apparently similar to that obtained in Iraq [2], Turkey [19], and Iran [20], lower than recorded in Ethiopia [21] and Egypt [22], and higher than carried out in India [23] and Jordan [24]. This variation in the prevalence of disease may reflect the different management systems, the amount of contamination of the pastures with the tapeworm eggs, and the attempts for controlling and preventing infection [25,26].…”
Section: Discussionsupporting
confidence: 91%
“…In Iraq, C. cerebralis is endemic in sheep and goats, resulting in direct economic losses due to morbidities and mortalities and indirect losses from low Available at www.veterinaryworld.org/Vol.14/June-2021/3.pdf carcass weight [2,12]; however, the rate of prevalence continues to be unknown because of the absence of molecular and epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before that, we installed data of the camels for determining the sex, age and periods. Transferring the samples in a cold box to the parasitology lab of the College of Veterinary Medicine, Al-Qadisiyah University, gross examination of the samples grossly for collecting the adults, isolated worms were taken by forceps to diagnose species of parasites, depending on the diagnostic characteristics described by (1,15). Molecular identification of the nematodes uses extracted of 20 rDNA isolates and traditional PCR technique with higher purity of DNA (16)(17)(18), PCR master mix prepared by using AccuPower® PCR PreMix Kit and this master mix done according to company instructions included: DNA template 5µl, Forward primer 1.5µl, Reveres primer 1.5µl and PCR water 12µl.…”
Section: Methodsmentioning
confidence: 99%
“…In Asia, enzootic coenurosis infections have been reported from India (2.9% in sheep) [ 49 ], Iran (1.7–18.6% in sheep and goats) [ 29 , 50 – 53 ], Bangladesh (2.5% in calves and 5% in Beetal goats) [ 54 , 55 ], Pakistan (0.4% in sheep and goats) [ 56 ], Japan [ 57 ] and Russia [ 58 ]. In the Middle East, cerebral coenurosis is a major endemic disease affecting small ruminants, most notably in Turkey, Egypt, Iraq, and Jordan [ 59 , 60 ], with prevalences of 2.9% in Jordanian sheep [ 61 ], 22.8–23.68% in Iraqi sheep and goats [ 62 , 63 ], 1.3–28.5% in Turkish sheep [ 64 , 65 ], and 16.6% in Dafuri goats in Oman [ 59 ]. A recent study in the El Menoufia Province of Egypt found C. cerebralis in 3.03% of sheep (26.4% of clinical cases) [ 66 ], which was significantly lower than the previously reported infection rates of 18–100% [ 14 , 67 ].…”
Section: Geographical Distribution and Epidemiologymentioning
confidence: 99%